ANALISIS USABILITY SISTEM INFORMASI PENERIMAAN MURID BARU DI KABUPATEN MUSI RAWAS MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) - Saputra, Arie; Yandi saputra, Arie; Eulis Bali Mawartika, Yayang (Al Ihsan Smart Cendekia, 2025)
This study aims to evaluate the usability level of the New Student Admission Information System (PMB) in Musi Rawas Regency using the System Usability Scale (SUS) method. The PMB system serves as a digital platform designed to facilitate the online registration process for new students. However, its implementation still faces several challenges, particularly in terms of ease of use and user comfort across different user groups. The research involved 50 respondents, categorized into three groups: 30 parents as external users, 15 school operators as technical implementers, and 5 education department staff as policy managers. Each respondent completed a SUS questionnaire consisting of 10 items on a 5-point Likert scale. The responses were analyzed through SUS score conversion and averaged per user group. The findings indicate varying usability levels among the user groups. Parents achieved an average SUS score of 44.5 (categorized as Poor), school operators 71.5 (Good), and education department staff 90.25 (Excellent). These results suggest that while the system is sufficiently effective for internal users, it remains less accessible and user-friendly for the general public, particularly parents who may have limited technological literacy. Based on these findings, improvements are recommended in terms of user interface design, availability of usage guidance, and mobile device optimization. Regular usability evaluations and active user involvement in system development are also advised to ensure sustainable and inclusive digital public services in the education sector.